Psychoeducation About Mental Health Problems on Family Emotional Support Patients After Schizophrenia Treatment - Novitasari, Novitasari; Safrudin, M Bachtiar; Imamah, Nur Fithriyanti (Sarana Ilmu Indonesia (salnesia), 2025)
To achieve a better recovery rate, patients with schizophrenia needed family support to help them become better individuals. One important form of support was emotional support, which helped patients feel comfortable, loved, and cared for, enabling them to cope with problems more effectively. Psychoeducation was an effective approach to improving emotional support and understanding of mental health issues, including schizophrenia. The objective of this study was to determine the effect of psychoeducation about mental health problems on the emotional support of family members of patients after schizophrenia treatment. This study involved one group using a pre-test and post-test design with a quantitative methodology. Purposive sampling was used to select 34 subjects in the working area of Wonorejo Health Center, and a questionnaire was used for data collection. The data were analyzed using a paired t-test. The results showed that most of the subjects were aged 41–50 years (41,2%), the majority were male (52,9%), most had a junior high school education (41,2%), the average duration of illness was 1–5 years (64,7%), and all subjects lived with their families (100,0%). The test results showed a p-value of <0,001, indicating that there is an effect of psychoeducation about mental health issues on the emotional support of families of patients after schizophrenia treatment. In conclusion, psychoeducation about mental health problems was effective in improving the emotional support of family members of patients after schizophrenia treatment.